Identifying investment priority areas for soil conservation in the Winike watershed, upper Omo Gibe Basin of Ethiopia - Abreham Berta Aneseyee; Eyasu Elias; Teshome Sorromessa (Watershed Ecology and the Environment, 2025)
Sustainable land management is necessary for soil erosion control, vegetation recovery, and land restoration. This study was conducted to identify the soil erosion susceptibility areas in the Winike watershed, upper Omo Gibe Basin of Ethiopia. Analytic Hierarchy Process (AHP) and InVEST modeling combined with GIS were used to generate primary data on soil erosion severity. Land use types, slope, elevation, NDVI, rainfall, drainage density, and soil types were important variables analyzed for soil erosion rate determination. The result shows a significant variation in soil erosion vulnerability among sub-watersheds ranging from low to very high vulnerability. The watershed’s very highly vulnerable eastern part accounts for 108.23 km2 (9.91 %) due to lacks vegetation cover, while the less vulnerable to the western part covers 179.66 km2 (16.46 %). Analysis of the Geo-environmental parameters shows that rainfall (26 %) is the most significant influencing factor, followed by vegetation cover (i.e., land use types), explaining about 23 % of the erosion severity. Comparing soil erosion vulnerability using the AHP and InVEST SDR models was 14.01 % and 16 %, respectively, suggesting insignificant variation between the erosion vulnerability analysis models. The study emphasizes the usefulness of erosion vulnerability modeling for identifying investment priority areas based on soil erosion status for soil conservation intervention, offering a range of decision-making options for land management.